2017
DOI: 10.31729/jnma.2930
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Complications in Acute Appendicitis among Paediatric Population

Abstract: Introduction: Appendicitis is one of the most common causes of acute abdomen in children. Patients who are diagnosed early and undergo an appendectomy before perforation have a good outcome. However, it is difficult to diagnose in young children because its clinical manifestations may be atypical. The aim of this study was to determine the risk factors for complications in acute appendicitis in paediatric population. Methods: We performed a cross sectional study on children (age ≤18 years) who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…At present, the preoperative assessment of using stress response indicators for CA were more confined to children with acute appendicitis, [12,30] but has been less reported in adults. The subject regards postoperative pathology as the standard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the preoperative assessment of using stress response indicators for CA were more confined to children with acute appendicitis, [12,30] but has been less reported in adults. The subject regards postoperative pathology as the standard.…”
Section: Discussionmentioning
confidence: 99%
“…[10] This was because the periappendiceal abscess often needs to be conservatively treated, such as the introduction of antibiotics or catheter drainage, [11] which is different from the treatment for acute gangrenous or perforated appendicitis. [12] In the present study, patients with periappendiceal abscess were excluded and not discussed for CA. This was because the CA in the present study refers to acute gangrenous appendicitis or perforated appendicitis.…”
Section: Introductionmentioning
confidence: 99%
“…The complete blood count (CBC) is one of the most commonly used laboratory tests for the diagnosis of AA. Many studies have focused on the role of white blood cell (WBC), neutrophil-to-lymphocyte ratio (NLR), platelet distribution width (PDW), mean platelet volume (MPV), red cell distribution width (RDW), platelet count (PLT), lymphocyte (L), neutrophil (N), C-reactive protein (CRP), and Lymphocyte-C-reactive protein ratio (LCR) values in the diagnosis of AA [4,8,[16][17][18]. We aimed to investigate the diagnostic efficacy of CBC parameters, CRP, and LCR in AA diagnosis and their relationship with appendix diameter.…”
Section: Introductionmentioning
confidence: 99%
“…APR stands at 10%, 44% and > 40% if appendicitis is diagnosed at 18 h, 36 h and > 48 h, respectively, from symptom onset. In comparison, Poudel and Bhandari ( 8 ) reported that patients with abdominal pain of > 72 h are more likely to have complicated appendicitis. Williams and Kapila ( 25 ) reported that fever is present in up to 90% of cases of appendicitis, and Siddique et al ( 9 ) reported that body temperature on admission is higher for patients with PA. Our study showed similar results.…”
Section: Discussionmentioning
confidence: 98%